Managing Cross-Border Crises in Southeast Asia at Multiple Levels of Governance: Complementary or Competitive Institutional Development at The National, ASEAN Regional, And EU-ASEAN Inter-Regional Levels? - Maier-Knapp, Naila (AEI Insights, 2021)
Although the multilateral moment attached to cross-border crises of the 21st century may have generally improved the palatability of regional integration to the member states of the Association of Southeast Asian Nations (ASEAN) and, in fact, induced integrative institutional dynamics at the national, ASEAN regional, and inter-regional level furthering the management of these concerns across multiple sectors and levels of governance outside day-to-day policies of the ASEAN member states, effective recognition of institutional integration that has been triggered by cross-border and transboundary crises takes place only to the extent that the political consequences remain controlled and compatible with the domestic politics of the ASEAN member states. Through the discussion of the institutional responses to the Asian financial crisis in 1997, the avian influenza outbreak at the end of 2003, and the Rohingya boat people crisis in 2015 this article makes the case for this domestic orientation and refers to institutional dynamics at the ASEAN regional and European Union (EU)-ASEAN inter-regional level with focus on questions of institutional cooperation, coordination, complementarity, correspondence, compatibility, and competition. It embeds these two levels of analysis in a broader multi-level setting encompassing the Thai national level and the broader global level to gain a better relational understanding of the crisis-oriented institutional dynamics of ASEAN regional and EU-ASEAN inter-regional integration.